2010
DOI: 10.5267/j.ijiec.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A discrete firefly meta-heuristic with local search for makespan minimization in permutation flow shop scheduling problems

Abstract: During the past two decades, there have been increasing interests on permutation flow shop with different types of objective functions such as minimizing the makespan, the weighted mean flow-time etc. The permutation flow shop is formulated as a mixed integer programming and it is classified as NP-Hard problem. Therefore, a direct solution is not available and metaheuristic approaches need to be used to find the near-optimal solutions. In this paper, we present a new discrete firefly meta-heuristic to minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(122 citation statements)
references
References 17 publications
(18 reference statements)
0
104
0
5
Order By: Relevance
“…The firefly algorithm can also participated in (42-44) (45), the fireflies also participated (46)(47)(48). firefly algorithm also involved for (49,50). Apart of all the above firefly algorithm (51).…”
Section: B Applications Areas Of Fire Fly Optimizationmentioning
confidence: 99%
“…The firefly algorithm can also participated in (42-44) (45), the fireflies also participated (46)(47)(48). firefly algorithm also involved for (49,50). Apart of all the above firefly algorithm (51).…”
Section: B Applications Areas Of Fire Fly Optimizationmentioning
confidence: 99%
“…Several discrete formulations of the FA have been applied to the discrete optimization problems in the context of operations management (Sayadi et al, 2010;Lu & Wang, 2016;Osaba et al, 2016;Zhou et al, 2015).…”
Section: Modified Discrete Firefly Algorithmmentioning
confidence: 99%
“…Therefore, we must replace this real number by a binary number. The following sigmoid function restricts x ik ð Þ to be in the interval of zero to one (Sayadi et al 2010):…”
Section: The Operators In Hcdfamentioning
confidence: 99%
“…The original firefly algorithm has been used for solving continuous optimization problems. Sayadi et al (2010) suggested a discrete firefly algorithm for flow shop scheduling problem. In fact, they modify the original firefly for discrete problems.…”
Section: Introductionmentioning
confidence: 99%